LAW ENFORCEMENT AGAINST THE CRIMINAL ACTION OF TRAFFICKING CHILDREN IN THE RIAU POLDA - Rio Satya Zulfahmi; Heni Susanti (Faculty of Law, Universitas Pekalongan, 2021)
Child trafficking is a form of crime that can be committed by a person or group of people or an institution against a person who is not yet 18 years old, including those who are still in the womb. A crime consists of a series of certain processes and for certain purposes. The purpose of this study was to determine the development of criminal acts of child trafficking in the Riau province from 2019 to 2021. To find out the efforts of the Riau regional police in dealing with child trafficking crimes in the Riau province. This study uses a sociological legal research method and the nature of this research is descriptive analysis and the approach method applied in this research is sociological juridical. This paper was developed through primary data collection techniques in the form of a number of information or facts directly obtained from the relevant agencies, namely the Riau Regional Police. Primary legal resources, secondary legal materials, and tertiary legal materials are among the two secondary data sources. In this research, the author employs the interview technique and the method of analysis for data collecting.Child trafficking is a form of crime that can be committed by a person or group of people or an institution against a person who is not yet 18 years old, including those who are still in the womb. A crime consists of a series of certain processes and for certain purposes. The purpose of this study was to determine the development of criminal acts of child trafficking in the Riau province from 2019 to 2021. To find out the efforts of the Riau regional police in dealing with child trafficking crimes in the Riau province. This study uses a sociological legal research method and the nature of this research is descriptive analysis and the approach method applied in this research is sociological juridical. This paper was developed through primary data collection techniques in the form of a number of information or facts directly obtained from the relevant agencies, namely the Riau Regional Police. Primary legal resources, secondary legal materials, and tertiary legal materials are among the two secondary data sources. In this research, the author employs the interview technique and the method of analysis for data collecting.